Anglican moral theology today. Issue 4 (November 2021) - Sedgwick, Peter
Anglican moral theology is a genealogy, in MacIntyre's use of this concept. It is a tradition that is handed on from one generation to another, practically and theoretically. Moral theology is part of the tradition of moral virtue, practiced by Christians, in local communities, families, and of course the church. What is distinctive in Anglicanism was that after 1580 there emerged an Anglican tradition of moral enquiry, which recognized the Protestant emphasis on scripture and a quite different role for the clergy, alongside a deep appreciation of the old, pre-Reformation tradition of moral theology. Today, the Anglican exemplary tradition also incorporates debates on sexuality, gender, and questions of identity. In social ethics, postcolonial voices show both the idolatry of political life and how our common life can be a locus of divine grace. Anglican moral theology is both very vibrant and deeply pluralist today.